Country-of-origin, Brand Image and Brand Loyalty of Branded Drugs in Ho Chi Ming City, Vietnam - Cheng, Raymond; Loan, La Thi Hong; Nguyen, Thai Hoa (2017)
While there has been numerous previous empirical studies investigating into a product’s country-of-origin (COO) and its relationship with various factors, including but not limited to brand loyalty, brand awareness and perceived quality, the findings were often inconsistent and differ from country to country (Kaynak & Kara, 2000). This is especially true when it comes to the pharmaceutical industry in which the importance of COO seems to depend on the type medicine studied and its use in addition to the usual factors for other non-medicine products (e.g. perceived quality, product evaluations other than quality, affect, and purchase intentions). This paper aims to look at the pharmaceutical market of Vietnam by studying the people’s brand awareness, brand loyalty, perceived quality and preferences toward COO of branded drugs available in the Ho Chi Ming City. Results show that Vietnamese, unlike Americans (as in Quelch’s (1997) Aspirin experiment), tend not be biased by brands but rather the COO, implying a very different market than some of its Asian neighbors.